Excellent mechanical properties of CoNiCr-based MP159 multicomponent alloys at ambient and cryogenic temperatures. (April 2023) - Wang, Dian; Pei, Biao; Wang, Zhong; Niu, Xiaofeng; Bi, Zhongnan; Qiao, Junwei; Gan, Bin
Abstract: The L12 -strengthened high-entropy alloys (HEAs) exhibit excellent mechanical properties. The commercial CoNiCr-based MP159 superalloy with high configuration entropy up to that of HEAs is revisited. And the coherent L12 nano precipitates with different sizes and volume fractions are introduced into MP159 alloys by tuning the aging time. Especially at 298 K, the alloys after aging for 10 h can achieve a good combination of 1360 MPa high tensile strength and 41% tensile strain. In contrast, the tensile strength is as high as 1710 MPa, and the tensile strain remains at 45% at cryogenic temperatures, much better than most of HEAs with similar composition. Importantly, the optimal size of the precipitates is calculated to be 41 nm. The present work provides a basic guidance for developing nano-precipitated CoNiCr-based alloys with high mechanical performances. Highlights: Different thermal-mechanical routes are designed to control the nucleation and growth of L12 precipitates in MP159 alloys to optimize their mechanical properties at ambient and cryogenic temperatures. At 77 K, YS and UTS of the aged alloys reached 1.2 GPa and 1.7 GPa respectively, and the tensile strain increased slightly to 45%, achieving a good combination of strength and ductility.